Psychological antecedents of vaccine inequity: keys to improve the rates of vaccination - Mohamed F. Hussein; Sarah A. Ibrahim; Suzan Abdel-Rahman; Abdelhamid Elshabrawy; Haqema A. A. Nasr; Saja Yazbek; Abdul Jabbar; Cinaria T. Albadri; Mariam Alsanafi; Narjiss Aji; Naglaa Youssef; Hammad M. Hammad; et al. (Journal of the Egyptian Public Health Association)
Abstract Background The World Health Organization (WHO) stresses the importance of worldwide vaccine coverage of coronavirus-19 (COVID-19) vaccination. This study fills a critical gap in the literature by providing empirical evidence on the factors influencing COVID-19 vaccine hesitancy and inequity in the Middle East and North Africa (MENA) region. This study investigated the determinants of psychological antecedents and other factors behind COVID-19 vaccination and their role in vaccine coverage in MENA. Methods An anonymous online cross-sectional survey was conducted in 11 MENA countries (Egypt, Sudan, Kuwait, Saudi Arabia, Morocco, Iraq, Yemen, Lebanon, Libya, Afghanistan, and Pakistan). The minimum required sample size from each country was 307, which was increased to 330 to accommodate a non-response rate of 7%. A multilevel logistic regression model was used to capture the clustering of observations in each country and estimate the explanatory variables’ effects on each item of the 5C components of the psychological antecedents scale namely (confidence, constraints, complacency, calculation, and collective responsibility). Results The total number of respondents was 3630, 40.5% of them were between the ages of 18 and 25 years, 61.1% were females, 54.0% completed university education, 55.8% were unmarried, 19.5% had chronic diseases, 43.7% reported a previous COVID-19 and 42.4% had relatives who died from COVID-19. Much of the variation in the log of the odds in each item of the 5Cs was due to heterogeneity between different countries (intraclass correlation > 0.05). Therefore, this variability confirms the various effects of psychological antecedents on vaccination coverage, stimulating vaccination inequity among them. Increasing confidence in vaccines and collective responsibility towards relatives and the community is related to increasing acceptance of the COVID-19 vaccine. The reduction in complacency, calculations, and constraints was found to be associated with acceptance of the COVID-19 vaccine. Conclusions This study is novel in shedding light on the importance of psychological determinants as hidden causes of vaccine inequities by using a multilevel logistic regression model for COVID-19 vaccination intention. The findings suggest that targeted interventions addressing socio-demographic factors, psychological antecedents, and accessibility barriers are essential to mitigate vaccine inequity and improve vaccination rates.